Aerogel composite material and preparation method and application thereof

CN122977812APending Publication Date: 2026-10-27DONGFENG MOTOR GRP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611128642.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0007]本发明提供了一种气凝胶复合材料及其制备方法和应用,旨在解决现有复合材料隔热与强度难以兼顾、高温易分层、制备成本高及无法规模化生产的问题

Benefits of technology

本发明采用常压梯度干燥工艺替代传统的超临界干燥工艺,通过优化升温速率与分段保温参数,能够解决常压干燥下气凝胶孔隙坍塌的技术难题。该工艺简单、操作便捷,无需复杂设备,使制备成本降低42%-48%,适合规模化生产,解决了现有气凝胶复合材料制备成本高、难以量产的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977812A_ABST
    Figure CN122977812A_ABST
Patent Text Reader

Abstract

The application discloses an aerogel composite material and a preparation method and application thereof, and belongs to the technical field of high-temperature thermal insulation materials. The aerogel composite material comprises a first layer and a second layer arranged oppositely and a gradient transition zone arranged between the first layer and the second layer. In the thickness direction from the first layer to the second layer, the content of a basalt fiber phase in the composite material decreases in a gradient manner, and the content of a silicon dioxide aerogel phase increases in a gradient manner. In the gradient transition zone, a nano transition layer is arranged at the interface between the basalt fiber phase and the silicon dioxide aerogel phase, and the nano transition layer comprises nano silicon dioxide and a silane coupling agent. The gradient structure design and the nano transition layer modification effectively take into account the thermal shock resistance on the high-temperature side and the thermal insulation performance on the low-temperature side of the material, are favorable for enhancing the interface bonding force, preventing high-temperature delamination, simultaneously reduce the preparation cost by adopting a normal-pressure gradient drying process, and are suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of high-temperature thermal insulation materials technology, specifically to an aerogel composite material, its preparation method, and its application. Background Technology

[0002] Aerogel materials, due to their unique nanoporous network structure, possess extremely low thermal conductivity and excellent thermal insulation properties, making them among the best-performing solid materials known to date. However, pure aerogel materials suffer from drawbacks such as low mechanical strength, high brittleness, susceptibility to shrinkage and cracking at high temperatures, and poor resistance to thermal shock, limiting their application in complex working conditions.

[0003] Basalt fiber, as an inorganic high-performance fiber, has advantages such as high temperature resistance, high mechanical strength, good chemical stability, and high cost performance. However, when used alone, basalt fiber has a relatively high thermal conductivity and limited thermal insulation performance, making it difficult to meet the needs of high-end and high-efficiency thermal insulation applications.

[0004] Existing technologies already exist for composite insulation materials combining basalt fibers and aerogel, aiming to combine the advantages of both. However, current composite methods are mostly uniform mixing or simple layered composites, failing to form an effective gradient structural distribution. This structure makes it difficult for the material to simultaneously achieve thermal shock resistance and temperature resistance at high temperatures and excellent thermal insulation performance at low temperatures. Furthermore, the interlayer bonding of existing composite materials is weak, making them prone to delamination and detachment during long-term high-temperature use above 800°C, affecting the material's service life and safety.

[0005] In terms of preparation technology, existing aerogel composite materials are mostly prepared using supercritical drying. Although this process can better maintain the pore structure of the aerogel, it requires sophisticated equipment, is complex, and is costly, making it unsuitable for large-scale production. While atmospheric pressure drying can reduce costs, capillary forces during the preparation process can easily cause pore collapse, resulting in a significant decrease in thermal insulation performance.

[0006] Therefore, how to develop a basalt-aerogel composite thermal insulation material that has excellent thermal insulation performance, high mechanical strength and high temperature resistance, while also having low preparation cost and being suitable for large-scale production, is a technical problem that needs to be solved by those skilled in the art. Summary of the Invention

[0007] This invention provides an aerogel composite material, its preparation method, and its application, aiming to solve the problems of existing composite materials, such as difficulty in achieving both thermal insulation and strength, easy delamination at high temperatures, high preparation costs, and inability to be mass-produced.

[0008] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides an aerogel composite material, the composite material comprising a first layer and a second layer disposed opposite to each other, and a gradient transition region disposed between the first layer and the second layer, wherein, along the thickness direction from the first layer to the second layer, the content of basalt fiber phase in the composite material decreases gradient and the content of silica aerogel phase increases gradient. In the gradient transition zone, a nano-transition layer is provided at the interface between the basalt fibrous phase and the silica aerogel phase. The nano-transition layer includes nano-silica and a silane coupling agent.

[0009] In some embodiments, the basalt fibrous phase in the first layer has a mass percentage of 62-78 wt%, and the silica aerogel phase has a mass percentage of 22-38 wt%.

[0010] In some embodiments, the basalt fiber phase in the second layer has a mass percentage of 25-47 wt%, and the silica aerogel phase has a mass percentage of 53%-75 wt%.

[0011] In some embodiments, the mass ratio of the nano-silica to the silane coupling agent in the nano-transition layer is 100:(7-13).

[0012] In some embodiments, the thickness of the nanotransition layer is 8-18 μm.

[0013] In some embodiments, the composite material also has a hierarchical pore gradient structure, and the pore size distribution of the hierarchical pore structure varies in a gradient along the thickness direction from the first layer to the second layer.

[0014] In some embodiments, in the first layer, the average pore size of the basalt fibrous phase is 65-185 μm, and the average pore size of the silica aerogel phase is 85-98 nm.

[0015] In some embodiments, in the second layer, the average pore size of the basalt fibrous phase is 120-280 μm, and the average pore size of the silica aerogel phase is 25-48 nm.

[0016] Secondly, the present invention provides a method for preparing the aforementioned aerogel composite material, comprising: Basalt fibers are mixed with a binder and a molding process is used to prepare a preform with a gradient distribution of basalt fiber content, resulting in a basalt fiber gradient preform. The preform has a first region and a second region that are arranged opposite to each other along the thickness direction. Nano-silica and silane coupling agent are dispersed in a solvent to obtain a nano-transition layer coating solution; The transition region between the first region and the second region is brought into contact with the nano-transition layer coating liquid, and then the preform is immersed in silica sol with a gradient concentration along the direction from the first region to the second region. The impregnated preform is then gelled to obtain a composite preform. The composite preform is dried using a gradient heating process to obtain the aerogel composite material.

[0017] In some embodiments, the molding process uses a pressing pressure of 0.7-1.3 MPa, a molding temperature of 105-118°C, and a holding time of 2.5-3.5 h.

[0018] In some embodiments, the concentration gradient distribution of the silica sol is specifically as follows: the sol concentration corresponding to the first region is 22-38 wt%, the sol concentration corresponding to the second region is 53-75 wt%, and the sol concentration corresponding to the transition region shows a gradient change.

[0019] In some embodiments, the impregnation process includes vacuum impregnation with a vacuum degree of -0.085 to -0.098 MPa.

[0020] In some embodiments, the drying process includes: raising the drying temperature from 50°C to 120°C at a rate of 6-9°C / h; and holding the temperature for 1.2-1.8h for every 20°C increase during the drying process until the moisture content of the composite green body is ≤0.9%.

[0021] Thirdly, the present invention provides a high-temperature thermal insulation component, which includes the aforementioned aerogel composite material, wherein the first layer is disposed facing the heat source direction.

[0022] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention employs an atmospheric pressure gradient drying process to replace the traditional supercritical drying process. By optimizing the heating rate and segmented heat preservation parameters, it solves the technical problem of aerogel pore collapse under atmospheric pressure drying. This process is simple, easy to operate, and requires no complex equipment, reducing preparation costs by 42%-48%. It is suitable for large-scale production and solves the problems of high preparation costs and difficulty in mass production of existing aerogel composite materials.

[0023] This invention improves the performance of aerogel composite materials through a synergistic gradient structure design of composition gradient, pore gradient, and nano-transition layer. The composition gradient addresses the balance between thermal insulation and strength, the pore gradient enhances thermal insulation, and the nano-transition layer overcomes weak interfacial bonding. The synergistic effect of these three elements results in aerogel composite materials with excellent temperature resistance, mechanical strength, and thermal insulation, while also exhibiting low bulk density and low water absorption.

[0024] This invention achieves precise control over the core performance parameters of aerogel composite materials through the synergistic combination of gradient preform molding and gradient impregnation processes. The resulting aerogel composite material exhibits a thermal conductivity of 0.021-0.024 W / (m·K) at 25℃, a compressive strength of 2.1-2.8 MPa, and can be used stably for extended periods at 800℃. This successfully overcomes the technical bottleneck of existing aerogel composite materials, which struggle to balance thermal insulation performance and mechanical strength. Therefore, the aerogel composite material provided by this invention can be widely applied in various fields such as aerospace, high-temperature equipment, metallurgy, chemical engineering, and building energy conservation, demonstrating significant practical value and promising application prospects. Attached Figure Description

[0025] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0026] Figure 1 This is a schematic diagram of the structure of the aerogel composite material provided in the embodiments of this application.

[0027] Figure 2 This is a magnified view of the interface between basalt fiber and silica aerogel.

[0028] Reference numerals: Aerogel composite material 100, first layer 10, gradient transition zone 20, basalt fiber phase 21, nano-transition layer 22, silica aerogel phase 23, second layer 30. Detailed Implementation

[0029] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some, not all, of the embodiments of this invention. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0030] Aerogels exhibit excellent thermal insulation performance due to their extremely low thermal conductivity, but their low mechanical strength, tendency to shrink and crack at high temperatures, and poor resistance to thermal shock limit their application alone. Basalt fiber, while possessing advantages such as high temperature resistance, high strength, and high cost-effectiveness, has limited thermal insulation performance when used alone, making it difficult to meet the needs of high-end and high-efficiency thermal insulation.

[0031] In existing technologies, basalt fiber and aerogel composites are mostly homogeneous mixtures or simple layered structures, resulting in a failure to simultaneously achieve thermal shock resistance at high temperatures and ultimate thermal insulation at low temperatures. Furthermore, the interlayer bonding is weak, making them prone to delamination and detachment under prolonged high temperatures, thus failing to meet long-term usage requirements above 800°C. In addition, existing preparation processes often balance the high cost of supercritical drying with the pore collapse associated with atmospheric pressure drying, making it difficult to achieve both large-scale production and performance stability.

[0032] Specifically, one existing technology uses ultrafine basalt fibers with a diameter of 3–5 μm to prepare low-density fiber mats. The fiber dispersion is improved by spraying a mixture of glycerol and sodium dodecylbenzenesulfonate, combined with a needle-punching process using a silane solution, and then impregnating the mat with aerogel sol to prepare a composite material. While this approach achieves low density and a service temperature above 700°C, the use of a single, uniform composite mode without differentiated design for high and low temperatures prevents the synergistic achievement of high-temperature impact resistance and low-temperature thermal insulation. Furthermore, the fiber mat and aerogel only undergo physical adsorption, resulting in weak interfacial bonding. The constant-temperature, ambient-pressure drying process causes rapid solvent evaporation and capillary pressure, leading to pore collapse. After 500 hours of use at 800°C, the thermal conductivity of the material rises to over 0.095 W / (m·K), indicating insufficient thermal insulation stability.

[0033] Another existing technology enhances the composite of basalt fiber and aerogel through interface modifiers and magnetron sputtering deposition of a titanium dioxide layer. While this approach improves interfacial bonding and mechanical properties, it still fails to overcome the structural limitations of uniform mixing and cannot address the performance differences between high and low temperatures. The interface modification does not fundamentally solve the problem of the large difference in thermal expansion coefficients between the fiber and aerogel, and delamination remains a risk in extreme environments above 800℃. Furthermore, because the drying process does not employ gradient heating and segmented insulation design, the regularity and stability of the aerogel's pore structure are insufficient, resulting in poor long-term thermal insulation performance of the material.

[0034] In summary, existing technologies still have shortcomings in terms of gradient structure design, interfacial bonding stability, and drying process control. Therefore, developing a basalt-aerogel composite thermal insulation material that combines excellent thermal insulation performance, mechanical strength, and high-temperature resistance, while also being low-cost and scalable, has become an urgent technical problem to be solved in this field.

[0035] In view of this, the present invention provides an aerogel composite material, its preparation method and application, aiming to solve the problems of existing composite materials that are difficult to balance heat insulation and strength, prone to delamination at high temperatures, have high preparation costs and cannot be mass-produced.

[0036] In a first aspect, the present invention provides an aerogel composite material 100. According to an embodiment of the present application, the composite material includes a first layer 10 and a second layer 30 disposed opposite to each other, and a gradient transition region 20 disposed between the first layer 10 and the second layer 30, wherein, along the thickness direction from the first layer 10 to the second layer 30, the content of basalt fiber phase 21 in the composite material decreases gradually, and the content of silica aerogel phase 23 increases gradually. In the gradient transition zone, a nano-transition layer 22 is provided at the interface between the basalt fiber phase 21 and the silica aerogel phase 23. The nano-transition layer 22 includes nano-silica and a silane coupling agent.

[0037] The aerogel composite material provided by this invention constructs a gradient distribution structure along the thickness direction, with a decreasing basalt fiber phase content and an increasing silica aerogel phase content. This allows the first layer to achieve excellent thermal shock resistance and temperature resistance due to its high basalt fiber content, while the second layer achieves low thermal conductivity due to its high aerogel content. This solves the problem that a single material cannot simultaneously achieve both high-temperature structural strength and low-temperature insulation efficiency. Furthermore, a nano-transition layer composed of nano-silica and silane coupling agent is set in the gradient transition region. The micro-filling effect of nano-silica and the chemical bonding effect of silane coupling agent are used to enhance the interfacial bonding force between the basalt fiber phase and the aerogel phase, effectively releasing the thermal stress caused by the difference in thermal expansion coefficients between the two phases. This prevents the material from undergoing interfacial delamination or cracking in long-term high-temperature environments above 800°C, ensuring the structural integrity and thermal insulation performance stability of the composite material under long-term high-temperature service conditions.

[0038] In some embodiments of the present invention, in the first layer 10, the mass percentage of the basalt fibrous phase is 62-78 wt%, and the mass percentage of the silica aerogel phase is 22-38 wt%. In the second layer 30, the mass percentage of the basalt fiber phase is 25-47 wt%, and the mass percentage of the silica aerogel phase is 53-75 wt%.

[0039] This invention ensures that the first layer 10 has sufficient fiber skeleton support by limiting the basalt fiber phase content to 62-78wt% and the silica aerogel phase content to 22-38wt%, thereby giving the composite material excellent thermal shock resistance and high-temperature structural stability. At the same time, the second layer 30 is limited to a basalt fiber phase content of 25-47wt% and a silica aerogel phase content of 53-75wt%, so that the second layer 30 is rich in aerogel to achieve excellent thermal insulation performance. With the gradient transition zone featuring a continuous decrease in basalt fiber phase content from 62-78 wt% to 25-47 wt% and a continuous increase in aerogel phase content from 22-38 wt% to 53-75 wt%, the thermal expansion coefficient and mechanical strength of the composite material can smoothly transition along the thickness direction. This eliminates the interlayer thermal stress concentration and mechanically weak layers in traditional double-layer abrupt structures, further improving the structural stability and vibration resistance of the composite material under high-temperature thermal cycling. At the same time, the aerogel phase content gradient is adapted to the temperature distribution along the material thickness direction, achieving synergistic optimization of temperature resistance and thermal insulation performance. Furthermore, the integrated continuous molding structure has no macroscopic interlayer interface, effectively avoiding the defects of easy debonding and peeling of laminated composite materials, and ensuring the performance stability of the composite material during long-term high-temperature service.

[0040] In some embodiments of the present invention, the mass ratio of nano-silica to silane coupling agent in the nano-transition layer 22 is 100:(7-13), and the thickness of the nano-transition layer 22 is 8-18 μm. By limiting the mass ratio of nano-silica to silane coupling agent in the nano-transition layer to 100:(7-13), it can be ensured that the silane coupling agent fully coats the nano-silica particles and forms a complete and continuous chemical bonded layer at the interface between basalt fiber and silica aerogel. The active groups at both ends of the silane coupling agent form covalent connections with the hydroxyl groups on the fiber surface and the silica-oxygen network of the aerogel, which is beneficial to improving the interfacial bonding strength. At the same time, it can avoid problems such as insufficient chemical bonding sites and limited interfacial reinforcement effect caused by too low a proportion of coupling agent, or weak boundary layer and agglomeration defects caused by too high a proportion of coupling agent.

[0041] With a transition layer thickness of 8-18μm, the transition layer can completely fill the tiny pores and gaps at the interface between the two phases, giving full play to the micro-filling effect of nano-silica, effectively buffering the thermal stress caused by the mismatch of thermal expansion coefficients between basalt fiber and aerogel. At the same time, it can avoid defects such as stress concentration and increased interface thermal conductivity caused by excessively thick transition layers, thus balancing the interface reinforcement effect and the overall thermal insulation performance of the material.

[0042] Therefore, it is used to improve the interfacial bonding between the basalt fibrous phase and the aerogel phase, and to prevent delamination and cracking at high temperatures.

[0043] It should be noted that the specific material of the nano-transition layer is not specifically limited in this application. For example, the nano-silica can be equivalently replaced by inorganic nanoparticles such as nano-alumina or nano-titanium oxide, with the particle size controlled within the range of 20-50 nm; the silane coupling agent can be equivalently replaced by coupling agents with similar functional groups such as KH-560 or KH-570. As long as the mixing ratio of nanoparticles to coupling agent is maintained within the range of 100:(7-13), the interfacial bonding force between the basalt fiber phase and the aerogel phase can be effectively improved, preventing high-temperature delamination and cracking, and the layer is basically consistent with the original nano-transition layer, all of which fall within the protection scope of this invention.

[0044] In some embodiments of the present invention, the composite material further has a multi-level pore gradient structure, and the pore size distribution of the multi-level pore structure varies in a gradient along the thickness direction from the first layer 10 to the second layer 30.

[0045] In some embodiments of the present invention, in the first layer 10, the average pore size of the basalt fibrous phase is 65-185 μm, and the average pore size of the silica aerogel phase is 85-98 nm; in the second layer, the average pore size of the basalt fibrous phase is 120-280 μm, and the average pore size of the silica aerogel phase is 25-48 nm.

[0046] This invention constructs a multi-level pore gradient structure, specifically defining the average pore size of the basalt fiber phase in the first layer 10 as 65-185 μm and the average pore size of the silica aerogel phase as 85-98 nm. The smaller basalt fiber pore size forms a denser skeleton, giving the first layer 10 higher structural strength to resist thermal shock. The silica aerogel phase pore size within this range ensures thermal insulation while maintaining gas permeability at high temperatures, preventing internal pressure buildup. The second layer 30 has an average pore size of 120-280 μm for the basalt fiber phase and an average pore size of 85-98 nm for the silica aerogel phase. The average pore size of the aerogel phase is 25-48 nm. Smaller silica aerogel pore size can enhance the Knudsen effect, which is beneficial to improving the thermal insulation efficiency of the second layer 30. Larger basalt fiber phase pore size helps to reduce material density. Combined with the continuous and gradual distribution of basalt fiber skeleton pore size and silica aerogel pore size in the gradient transition zone, the uneven heat flux density and stress concentration caused by abrupt pore size changes are eliminated, achieving a synergistic improvement in thermal insulation performance and air permeability, ensuring the thermal management efficiency and structural stability of the composite material in a wide temperature range.

[0047] It should be noted that "average pore size of basalt fibrous phase" refers to the pores in the fibrous phase.

[0048] In some embodiments of the present invention, the main component of the basalt fiber phase is basalt fiber, with a fiber diameter of 3-8 μm, a length of 5-15 mm, and a fiber purity of ≥98%. To improve the dispersibility of the fiber in the slurry and avoid fiber agglomeration due to electrostatic effects during preparation, 0.5-1.5 wt% of an antistatic agent, such as sodium dodecylbenzenesulfonate, is added to the basalt fiber phase. This addition helps ensure the uniformity of the fiber skeleton structure, thereby guaranteeing the mechanical strength and pore distribution stability of the material. Furthermore, the surface of the basalt fiber is pretreated with a silane coupling agent, which further enhances the interfacial bonding between the basalt fiber phase and the silica aerogel phase through surface modification, reducing the risk of interfacial defects.

[0049] In other embodiments of the present invention, the basalt fiber phase can also be replaced by basalt fiber felt or basalt fiber cloth instead of loose basalt fibers. The areal density of the basalt fiber felt can be selected as 300-500 g / m², and the thickness of the basalt fiber cloth can be selected as 0.1-0.3 mm. All of the above-mentioned alternative materials can achieve the same functions of skeletal support, high-temperature resistance, and enhanced mechanical strength. During the preparation process, the gradient composition ratio can remain unchanged; only the layup method during preform preparation needs to be adjusted, for example, by controlling the stacking quantity and order of different layers of fiber felt or cloth, to ensure that the final product meets the requirements of gradient content distribution.

[0050] In some embodiments of the present invention, the silica aerogel phase comprises silica aerogel with a purity ≥99%. To regulate the gelation process and improve structural stability, 0.3-0.8 wt% of a curing agent is added to the aerogel phase, exemplarily ammonia solution with a concentration of 25-28 wt%, which helps accelerate the in-situ gelation rate of the aerogel. Furthermore, to enhance the high-temperature flame retardant properties of the composite material, 0.2-0.5 wt% of a flame retardant, such as aluminum hydroxide, is added, which helps suppress the combustion tendency of the composite material under high-temperature conditions and reduce the release of harmful gases. During the aerogel preparation process, 0.1-0.3 wt% of a surfactant, such as Tween-80, can also be added to optimize the pore structure formation of the aerogel, thereby further reducing the thermal conductivity of the material.

[0051] In other embodiments of the present invention, the silica aerogel can be replaced with a silica-alumina composite aerogel or a silica-zirconia composite aerogel. Specifically, when using a silica-alumina composite aerogel, the alumina content is 5-15 wt%; when using a silica-zirconia composite aerogel, the zirconia content is 3-10 wt%. Using the above composite aerogel system can further improve the high-temperature resistance of the material, increasing the long-term service temperature to 900-1050℃, while maintaining properties such as thermal conductivity and mechanical strength that are essentially the same as those of the pure silica aerogel solution, thus achieving the thermal insulation and structural support functions required by the present invention.

[0052] Secondly, the present invention provides a method for preparing the aforementioned aerogel composite material. According to an embodiment of this application, the preparation method includes the following steps: S100: Preparation of basalt fiber gradient preforms.

[0053] In this step, basalt fibers are mixed with a binder, and a preform with a gradient distribution of basalt fiber content is prepared by a molding process to obtain a basalt fiber gradient preform. The preform has a first region and a second region that are arranged opposite to each other along the thickness direction.

[0054] Specifically, basalt fibers are mixed with a binder, which is a sodium silicate solution with a concentration of 6-9 wt%. This concentration range ensures that the sodium silicate binder has sufficient adhesive force, effectively bonding and shaping the basalt fibers in each layer, maintaining a gradient distribution of fiber content along the thickness direction of the preform, and preventing fiber loosening and layer mixing during subsequent sol impregnation. Through a layered web-laying process, the amount of fiber laid in different layers is controlled, resulting in a gradient distribution of basalt fiber content that gradually decreases from the first region to the second region along the thickness direction of the preform.

[0055] Subsequently, the preform is pressed and molded, with the pressing pressure controlled at 0.7-1.3 MPa. This pressure range ensures that the preform achieves sufficient density and structural strength, preventing deformation and delamination during handling and subsequent impregnation processes, and maintaining the distribution accuracy of the gradient fibers.

[0056] The molding temperature is set at 105-118℃, and the holding time is 2.5-3.5h. These process parameters allow the moisture in the binder to evaporate evenly and fully, and the sodium silicate binder to cure evenly and completely. This ensures that the preform has stable dimensions and sufficient dry strength, while avoiding cracking and warping caused by excessive temperature or excessively fast drying. At the same time, it prevents over-curing from introducing excessive brittle phases, ensuring the structural integrity of the preform and its compatibility with subsequent processes. It also provides a structurally stable and precisely gradient fiber skeleton substrate for the subsequent aerogel composite process.

[0057] Thus, through the above steps, a basalt fiber gradient preform with a first region and a second region set in a relative manner is obtained.

[0058] It should be noted that this application does not specifically limit the molding method of the preform. Besides the layered mesh laying combined with pressing molding described above, centrifugal molding or spray molding processes can also be used. For example, when using centrifugal molding, the rotation speed is controlled at 1000-1500 r / min, and the molding time is 10-20 min; when using spray molding, the spray pressure is controlled at 0.3-0.5 MPa. All of the above alternative processes can produce basalt fiber gradient preforms with uniform gradient content distribution, and the pore structure and mechanical strength of the preforms after molding are basically consistent with those of the layered mesh laying process, while also helping to improve production efficiency.

[0059] S200: Preparation of nano-transition layer coating liquid.

[0060] In this step, nano-silica and silane coupling agent are dispersed in a solvent to obtain a nano-transition layer coating solution.

[0061] Specifically, nano-silica with a particle size of 25-45 nm and silane coupling agent KH-550 are added to deionized water, and the concentration of nano-silica is controlled at 12-18 wt%.

[0062] By limiting the particle size range of nano-silica to the above range, it is possible to ensure that the size of the nanoparticles is adapted to the micro-pits on the surface of basalt fiber and the tiny gaps at the interface between the two phases, giving full play to the interface micro-filling effect and reducing interface porosity defects; at the same time, the thermal expansion coefficient of the transition layer formed by particles in this particle size range is between that of basalt fiber and silica aerogel, which can better buffer the thermal stress between the two phases.

[0063] Limiting the concentration of nano-silica to the range of 12-18 wt% allows the coating solution to maintain suitable viscosity and solid content. A single coating can form a continuous and uniform nano-transition layer with the required thickness on the fiber surface, matching the thickness design requirement of 8-18 μm. At the same time, this concentration range is more conducive to maintaining the dispersion stability of the coating solution and reducing the risk of particle sedimentation and agglomeration.

[0064] During the mixing process, stirring combined with ultrasonic dispersion for 35-55 minutes breaks up the agglomerates of nano-silica, allowing it to achieve a monodisperse state in the solvent, thus ensuring the structural uniformity and stability of the coating solution. Through these steps, a uniformly dispersed and highly stable nano-transition layer coating solution can be obtained.

[0065] S300: Gradient impregnation aerogel sol.

[0066] In this step, the transition region between the first region and the second region is brought into contact with the nano-transition layer coating liquid, and then the preform is immersed in silica sol with a gradient concentration along the direction from the first region to the second region.

[0067] Specifically, the transition region of the basalt fiber gradient preform is immersed in the nano-transition layer coating solution for a controlled immersion time of 1.2-1.8 hours. This time range ensures that the nano-transition layer coating solution fully penetrates the pores of the gradient fiber skeleton and the interfacial gaps in the transition region, forming a uniform and continuous nano-transition layer with a stable thickness within the designed range of 8-18 μm on the fiber surface. This ensures the uniformity and continuity of the interfacial reinforcement effect throughout the entire thickness of the transition region. After removal and drying, the preform is sequentially immersed in silica sol with a gradient concentration along the direction from the first region to the second region.

[0068] Specifically, the sol concentration in the first region is controlled at 22-38 wt%, the sol concentration in the second region is controlled at 53-75 wt%, and the sol concentration in the transition region changes continuously and gradually. This concentration gradient design matches the fiber content gradient of the preform. The lower sol concentration in the first region can retain more fiber skeleton to enhance thermal shock resistance, while the higher sol concentration in the second region fills more aerogel to improve thermal insulation.

[0069] Vacuum assistance is employed during the impregnation process, maintaining a vacuum level of -0.085 to -0.098 MPa. This vacuum level effectively removes residual air from the pores of the basalt fiber gradient precast body, eliminating air bubble obstruction and ensuring that the silica sol fully and uniformly penetrates the micropores of the fiber skeleton in each region, including the gradient pores in the transition zone. This ensures a precise match between the aerogel filling amount and the gradient concentration design. The impregnation time for each segment is set to 2.2-2.8 hours, ensuring that silica sol of different concentrations fully penetrates into the fiber skeleton of the corresponding region, achieving the designed aerogel filling ratio and matching the performance positioning of high thermal shock resistance in the first region and high thermal insulation in the second region.

[0070] In other embodiments of the present invention, pressure impregnation can be used instead of vacuum impregnation. Specifically, the pressure is controlled at 0.2-0.4 MPa, and the impregnation time remains constant at 2.2-2.8 h. Pressure impregnation utilizes positive pressure to drive sol penetration, which can also ensure that the aerogel sol fully fills the gaps between basalt fibers to form a uniform composite structure. Moreover, the equipment is relatively simple to operate and can achieve the same technical effect as vacuum impregnation.

[0071] S400: In-situ gel.

[0072] In this step, the impregnated preform is gelled to obtain a composite preform.

[0073] Specifically, the impregnated gradient preform is placed in a constant temperature and humidity environment, with the ambient temperature controlled at 28-32℃ and the relative humidity at 65-75%, and left to stand for 4.5-5.5 hours.

[0074] Selecting a temperature range of 28-32℃ can make the hydrolysis and polycondensation reaction rate of silica sol stable and controllable. This avoids slow gelation and significantly prolonged cycle caused by excessively low temperature, while also preventing localized rapid gelation caused by excessively high temperature, which would result in uneven cross-linking of the gel within the preform and collapse of pores. This ensures that the sol in each gradient region solidifies synchronously and uniformly.

[0075] Maintaining humidity at 65-75% can inhibit the rapid evaporation of solvents inside the sol, prevent premature drying and peeling of the surface of the preform, blockage of internal pores, maintain a stable reaction environment for the system, and ensure full bonding between the nano-transition layer at the fiber interface and the silica sol.

[0076] Setting the settling time to 4.5-5.5 hours allows silica sols of different concentration gradients to fully cross-link and solidify, forming a continuous and complete three-dimensional aerogel network. This avoids incomplete cross-linking and low wet gel strength due to insufficient settling time, which could lead to structural collapse in subsequent processes. It also avoids excessive cross-linking due to prolonged settling, which could increase internal stress and cause microcracks in the green body.

[0077] Therefore, this experimental procedure can achieve in-situ aerogel gelation, forming a basalt-aerogel gradient composite preform.

[0078] S500: Atmospheric pressure gradient drying.

[0079] In this step, the composite preform is dried using a gradient heating process to obtain the aerogel composite material.

[0080] Specifically, the composite preform is placed in a drying oven and subjected to a gradient heating program from 50°C to 120°C. The heating rate is controlled at 6-9°C / h, allowing the solvent inside the preform to slowly and uniformly precipitate outwards. This avoids excessively rapid heating that could cause the solvent to vaporize rapidly, generating huge capillary stresses that could lead to aerogel pore collapse and preform cracking and deformation. Simultaneously, it prevents excessively low heating rates from prolonging the production cycle, balancing pore integrity with industrial production efficiency.

[0081] Simultaneously, a segmented heat preservation strategy is adopted, i.e., holding the temperature for 1.2-1.8 hours for every 20℃ increase. This ensures uniform temperature throughout the green body along its thickness direction, simultaneously releasing solvents from different gradient regions, eliminating the moisture content difference between the core and surface of the green body, alleviating thermal stress concentration, and further protecting the multi-level porous gradient structure and the nano-transition layer at the two-phase interface from damage, ensuring stable and deformation-free distribution of gradient components. The drying endpoint is controlled at a green body moisture content ≤0.9% to ensure complete solvent removal, resulting in an aerogel composite material with an intact skeleton and stable thermal insulation performance.

[0082] Thirdly, this application provides a high-temperature thermal insulation component. According to an embodiment of this application, the high-temperature thermal insulation component includes the aerogel composite material described in the first aspect, or an aerogel composite material prepared by the method described in the second aspect, wherein the first layer is disposed facing the heat source. The high-temperature thermal insulation component possesses all the technical solutions of the aerogel composite material, and therefore also possesses all the beneficial effects of the aerogel composite material, which will not be elaborated upon here.

[0083] The technical solution provided by the present invention will be described in detail below with reference to the embodiments.

[0084] Unless otherwise specified, the raw materials used in the examples and comparative examples are commercially available analytical grade materials.

[0085] Example 1 This embodiment provides an aerogel composite material. The composite material comprises, along its thickness direction, a first layer, a gradient transition zone, and a second layer. The first layer contains 68 wt% basalt fiber phase and 32 wt% silica aerogel phase, with a fiber skeleton pore size range of 90-145 μm and an aerogel pore size range of 88-96 nm. The second layer contains 35 wt% basalt fiber phase and 65 wt% silica aerogel phase, with a fiber skeleton pore size range of 160-240 μm and an aerogel pore size range of 28-45 nm. Within the gradient transition zone, each basalt fiber surface is coated with a nano-transition layer. This nano-transition layer, located at the microscopic interface between the basalt fiber phase and the silica aerogel phase, is 12 μm thick and is composed of nano-silica and silane coupling agent KH-550 at a mass ratio of 100:11.

[0086] The preparation process of this aerogel composite material includes the following steps: (1) Preparation of basalt fiber gradient preform: Basalt fibers were mixed with a 7 wt% sodium silicate solution according to the designed ratio, wherein the basalt fiber content in the first side region was 68%, the basalt fiber content in the second side region was 35%, and the transition zone showed a layered and gradually changing distribution. After the mixture was layered and laid into a web, it was placed in a mold and pressed at 1.1 MPa pressure and 112℃ temperature for 3.2 h to obtain a basalt fiber preform with a gradient structure.

[0087] (2) Preparation of nano-transition layer coating solution: Nano-silica with a particle size of 32 nm was prepared into a dispersion with a concentration of 16 wt%, and silane coupling agent KH-550 was added. The mass ratio of nano-silica to KH-550 was controlled to be 100:11. After adding deionized water, the mixture was ultrasonically dispersed for 48 min to obtain a uniform coating solution.

[0088] (3) Gradient impregnation with aerogel sol: The transition zone of the preform was immersed in the nano-transition layer coating solution for 1.6 h, and then removed and dried. Subsequently, the preform was sequentially immersed in silica aerogel sol with a concentration gradient distribution (initial concentration of 32 wt% in the first region and final concentration of 65 wt% in the second region) along the direction from the first side region to the second side region. Each impregnation process was carried out under a vacuum of -0.092 MPa for 2.6 h to ensure that the sol fully penetrated.

[0089] (4) In-situ gelation: The impregnated preform is transferred to an environment with a temperature of 31°C and a relative humidity of 72% and left to stand for 5.2 h to allow the sol to complete in-situ gelation within the fiber skeleton and form a composite preform.

[0090] (5) Atmospheric pressure gradient drying: The composite preform is placed in a drying oven and dried using a gradient heating process. The temperature is raised from 50℃ to 120℃, the heating rate is controlled at 8.5℃ / h, and the temperature is maintained for 1.6 h for every 20℃ increase, until the moisture content of the preform drops to 0.75%, and finally the basalt-aerogel gradient composite thermal insulation material is obtained.

[0091] Example 2 This embodiment provides a basalt-aerogel gradient composite thermal insulation material. The material comprises, along its thickness direction, a first layer, a gradient transition zone, and a second layer. Specifically, the first layer contains 75 wt% basalt fiber phase and 25 wt% silica aerogel phase; the basalt fiber phase has a pore size range of 68-95 μm, and the silica aerogel phase has a pore size range of 92-98 nm. The second layer contains 28 wt% basalt fiber phase and 72 wt% silica aerogel phase; the basalt fiber phase has a pore size range of 210-270 μm, and the silica aerogel phase has a pore size range of 25-42 nm. Within the gradient transition zone between the first and second layers, each basalt fiber surface is coated with a nano-transition layer. The nano-transition layer is located at the microscopic interface between the basalt fiber phase and the silica aerogel phase. The thickness of the nano-transition layer is 14 μm, and it is composed of nano-silica and silane coupling agent KH-550 in a mass ratio of 100:12.5.

[0092] The preparation method in this embodiment is basically the same as that in Example 1, with the main process parameters adjusted as follows: (1) Preparation of basalt fiber gradient preform: Basalt fibers were mixed with a 7 wt% sodium silicate solution according to the designed ratio, wherein the basalt fiber phase accounted for 75% in the first region and 28% in the second region, and the transition region showed a layered and gradually changing distribution. After the mixture was layered and laid into a web, it was placed in a mold and pressed at 1.1 MPa pressure and 112℃ temperature for 3.2 h to obtain a basalt fiber preform with a gradient structure.

[0093] (2) Preparation of nano-transition layer coating solution: Nano-silica with a particle size of 32 nm was prepared into a dispersion with a concentration of 16 wt%, and silane coupling agent KH-550 was added. The mass ratio of nano-silica to KH-550 was controlled to be 100:12.5. After adding deionized water, the mixture was ultrasonically dispersed for 48 min to obtain a uniform nano-transition layer coating solution.

[0094] (3) Gradient impregnation with aerogel sol: The transition zone of the preform was immersed in the nano-transition layer coating solution for 1.6 h, and then removed and dried. Subsequently, the preform was sequentially immersed in silica aerogel sol with a concentration gradient distribution (initial concentration of 25 wt% in the first region and final concentration of 72 wt% in the second region) along the direction from the first region to the second region. Each impregnation process was carried out under a vacuum of -0.092 MPa for 2.6 h.

[0095] (4) In-situ gelation: The impregnated preform is transferred to an environment with a temperature of 31°C and a relative humidity of 72% and left to stand for 5.2 h to allow the sol to complete in-situ gelation within the fiber skeleton and form a composite preform.

[0096] (5) Atmospheric pressure gradient drying: The composite preform is placed in a drying oven and dried using a gradient heating process. The temperature is raised from 50℃ to 120℃, the heating rate is controlled at 9.5℃ / h, and the temperature is maintained for 1.6 h for every 20℃ increase, until the moisture content of the preform drops to 0.75%, and finally the basalt-aerogel gradient composite thermal insulation material is obtained.

[0097] Example 3 This embodiment provides a basalt-aerogel gradient composite thermal insulation material. The material comprises, along its thickness direction, a first layer, a gradient transition zone, and a second layer. The first layer contains 62 wt% basalt fiber phase and 38 wt% silica aerogel phase, with the basalt fiber phase having a pore size range of 65-95 μm and the silica aerogel phase having a pore size range of 92-98 nm. The second layer contains 25 wt% basalt fiber phase and 75 wt% silica aerogel phase, with the basalt fiber phase having a pore size range of 210-280 μm and the silica aerogel phase having a pore size range of 25-42 nm. Within the gradient transition zone between the first and second layers, each basalt fiber surface is coated with a nano-transition layer. The nano-transition layer is located at the microscopic interface between the basalt fiber phase and the silica aerogel phase. The thickness of the nano-transition layer is 8 μm, and it is composed of nano silica and silane coupling agent KH-550 in a mass ratio of 100:13.

[0098] The preparation method in this embodiment is basically the same as that in Example 1, with the main process parameters adjusted as follows: (1) Preparation of basalt fiber gradient preform: Basalt fibers were mixed with a 6 wt% sodium silicate solution according to the designed ratio, wherein the basalt fiber phase accounted for 62 wt% in the first region and 25 wt% in the second region, and the transition region showed a layered and gradually changing distribution. After the mixture was layered and laid into a web, it was placed in a mold and pressed at 0.7 MPa pressure and 105℃ temperature for 2.5 h to obtain a basalt fiber preform with a gradient structure.

[0099] (2) Preparation of nano-transition layer coating solution: Nano-silica with a particle size of 25 nm is prepared into a dispersion with a concentration of 12 wt%, silane coupling agent KH-550 is added, the mass ratio of nano-silica to KH-550 is controlled to be 100:13, deionized water is added and ultrasonically dispersed for 35 min to obtain a uniform nano-transition layer coating solution.

[0100] (3) Gradient impregnation with aerogel sol: The transition zone of the preform was immersed in the nano-transition layer coating solution for 1.2 h, and then removed and dried. Subsequently, the preform was sequentially immersed in silica aerogel sol with a concentration gradient distribution (initial concentration of 38 wt% in the first region and final concentration of 75 wt% in the second region) along the direction from the first region to the second region. Each impregnation process was carried out under a vacuum of -0.085 MPa for 2.2 h.

[0101] (4) In-situ gelation: The impregnated preform is transferred to an environment with a temperature of 28°C and a relative humidity of 65% and left to stand for 4.5 h to allow the sol to complete in-situ gelation within the fiber skeleton and form a composite preform.

[0102] (5) Atmospheric pressure gradient drying: The composite preform is placed in a drying oven and dried using a gradient heating process. The temperature is raised from 50℃ to 120℃, the heating rate is controlled at 6℃ / h, and the temperature is maintained for 1.2 h for every 20℃ increase, until the moisture content of the preform drops to 0.75%, and finally the basalt-aerogel gradient composite thermal insulation material is obtained.

[0103] Example 4 This embodiment provides an aerogel composite material. The composite material comprises, along its thickness direction, a first layer, a gradient transition zone, and a second layer. The first layer has a basalt fiber phase content of 78 wt% and a silica aerogel phase content of 22 wt%, with a fiber skeleton pore size range of 90-185 μm and an aerogel pore size range of 85-96 nm. The second layer has a basalt fiber phase content of 47 wt% and a silica aerogel phase content of 53 wt%, with a fiber skeleton pore size range of 120-240 μm and an aerogel pore size range of 28-48 nm. Within the gradient transition zone between the first and second layers, each basalt fiber surface is coated with a nano-transition layer. This nano-transition layer is located at the microscopic interface between the basalt fiber phase and the silica aerogel phase. The transition layer has a thickness of 18 μm and is composed of nano-silica and a silane coupling agent KH-550 at a mass ratio of 100:7.

[0104] The preparation method in this embodiment is basically the same as that in Example 1, with the main process parameters adjusted as follows: (1) Preparation of basalt fiber gradient preform: Basalt fibers were mixed with a 9wt% sodium silicate solution according to the designed ratio, wherein the basalt fiber content in the first side region was 78%, the basalt fiber content in the second side region was 47%, and the transition zone showed a layered and gradually changing distribution. After the mixture was layered and laid into a web, it was placed in a mold and pressed at 118℃ for 3.5 h under a pressure of 1.3 MPa to obtain a basalt fiber preform with a gradient structure.

[0105] (2) Preparation of nano-transition layer coating solution: Nano-silica with a particle size of 45 nm is prepared into a dispersion with a concentration of 18 wt%. Silane coupling agent KH-550 is added, and the mass ratio of nano-silica to KH-550 is controlled to be 100:7. After adding deionized water, it is ultrasonically dispersed for 55 min to obtain a uniform coating solution.

[0106] (3) Gradient impregnation with aerogel sol: The transition zone of the preform was immersed in the nano-transition layer coating solution for 1.8 h, and then removed and dried. Subsequently, the preform was sequentially immersed in silica aerogel sol with a concentration gradient distribution (initial concentration of 22 wt% in the first region and final concentration of 53 wt% in the second region) along the direction from the first region to the second region. Each impregnation process was carried out under a vacuum of -0.098 MPa for 2.8 h.

[0107] (4) In-situ gelation: The impregnated preform is transferred to an environment with a temperature of 32°C and a relative humidity of 75% and left to stand for 5.5 h to allow the sol to complete in-situ gelation within the fiber skeleton and form a composite preform.

[0108] (5) Atmospheric pressure gradient drying: The composite preform is placed in a drying oven and dried using a gradient heating process. The temperature is raised from 50℃ to 120℃, the heating rate is controlled at 6℃ / h, and the temperature is maintained for 1.8h for every 20℃ increase, until the moisture content of the preform drops to 0.75%, and finally the basalt-aerogel gradient composite thermal insulation material is obtained.

[0109] Comparative Example 1 This comparative example provides a uniform composite thermal insulation material. The difference from Example 1 is that no gradient structure is provided; basalt fibers and aerogel are uniformly distributed throughout the material's thickness direction, with a basalt fiber phase content of 50 wt% and an aerogel phase content of 50 wt%. Furthermore, no nano-transition layer is provided; the fiber felt is directly impregnated in the aerogel sol. The drying process employs constant temperature and ambient pressure drying, with the temperature directly set at 110℃ and held for 5 hours.

[0110] Comparative Example 2 The difference between this comparative example and Example 1 is that no nano-transition layer is provided. That is, the contact treatment of the nano-transition layer coating liquid is omitted in steps (2) and (3), and the preform is directly immersed in the aerogel sol. The remaining composition and preparation process are the same as in Example 1.

[0111] Comparative Example 3 The difference between this comparative example and Example 1 is that the drying process uses conventional constant temperature drying. The drying temperature is directly set to 120℃, and the holding time is 6 hours, without gradient heating or segmented holding steps. The remaining composition and preparation process are the same as in Example 1.

[0112] Performance testing The aerogel composite materials of Examples 1-4 and Comparative Examples 1-3 were subjected to performance tests. The specific test methods were as follows: 1. Thermal conductivity test: (1) Thermal conductivity at room temperature of 25℃: The steady-state protective hot plate method was adopted, and the test was carried out in accordance with GB / T 10294-2008 "Determination of steady-state thermal resistance and related properties of thermal insulation materials - protective hot plate method". The sample size was 150mm×150mm×20mm, the temperature difference between the hot and cold surfaces was set at 15℃, and the average temperature of the sample was 25℃. After the heat flow stabilized, the data was recorded and the room temperature thermal conductivity of the sample was calculated.

[0113] (2) Thermal conductivity at 800℃: The hot wire method was used, and the test was conducted in accordance with GB / T 17911-2018 "Test Methods for Refractory Fiber Products". The sample size was 230mm×114mm×25mm. The sample was heated to 800℃ in an air atmosphere and kept at that temperature for 30 minutes. After the temperature stabilized, the thermal conductivity at high temperature was tested.

[0114] 2. Temperature resistance test: (1) Long-term service temperature: The sample with dimensions of 100mm×100mm×20mm was placed in a muffle furnace and kept at 650℃, 700℃, 750℃, 800℃, 850℃, 900℃, 950℃ and 1000℃ for 200h respectively. After being taken out and naturally cooled to room temperature, its thermal conductivity and mass change were tested. The highest temperature at which the thermal conductivity increased by ≤10%, the mass loss was ≤5%, and there was no obvious cracking or pulverization was taken as the long-term service temperature of the material.

[0115] (2) Short-term use temperature: Place the sample with dimensions of 100mm×100mm×20mm into a muffle furnace preheated to the set temperature, keep it at a constant temperature for 2 hours, and then take it out and air cool it to room temperature. Observe the appearance of the sample. The highest temperature at which the sample has no macroscopic cracks, no powdering and peeling, and a thickness shrinkage rate of ≤2% is the short-term use temperature of the material.

[0116] (3) Heat shrinkage under constant temperature of 800℃ for 1000h: First test the thickness and side length of the sample in the initial state (accuracy 0.01mm), put the sample into the muffle furnace at 800℃ and keep it at constant temperature for 1000h, take it out and let it cool naturally to room temperature, and then test the corresponding dimensions again; calculate the heat shrinkage rate in the thickness direction and the planar direction respectively according to the formula "heat shrinkage rate = (initial size - final size) / initial size × 100%".

[0117] 3. Mechanical strength test: (1) Compressive strength: The test was conducted in accordance with GB / T 13480-2014 "Determination of compressive properties of thermal insulation products for building". The sample was a cube of 50mm×50mm×50mm. A universal testing machine was used to compress the sample at a rate of 2mm / min. The stress value when the sample thickness was compressed by 10% was recorded, which is the compressive strength of the material.

[0118] (2) Tensile strength: The test was conducted in accordance with GB / T 5486-2008 "Test Methods for Inorganic Rigid Thermal Insulation Products". The specimen was a cuboid of 50mm×50mm×20mm. The two ends of the specimen were bonded to the tensile fixture with a high-temperature adhesive. The specimen was stretched at a rate of 1mm / min. The maximum tensile force at which the specimen broke was recorded. The tensile strength was calculated according to the formula "Tensile strength = Maximum tensile force / Cross-sectional area of ​​specimen".

[0119] (3) Bending strength: The three-point bending method was adopted and the test was carried out in accordance with GB / T 6569-2006 "Test Method for Bending Strength of Fine Ceramics". The sample size was 120mm×30mm×15mm, the test span was 90mm, the loading rate was 1mm / min, the maximum load when the sample broke was recorded, and the bending strength was calculated according to the formula "bending strength = 3FL / (2bh²)" (F is the maximum load, L is the span, b is the sample width, and h is the sample thickness).

[0120] 4. Other performance tests: (1) Bulk density: The test was conducted in accordance with GB / T 5486-2008 "Test Methods for Inorganic Rigid Thermal Insulation Products". The sample was a cuboid of 100mm×100mm×50mm. After drying to constant weight, the mass was weighed, the volume of the sample was measured and calculated, and the bulk density was calculated according to the formula "bulk density = dry weight of sample / volume of sample".

[0121] (2) Water absorption rate: The water immersion method at room temperature is used for testing. Weigh the sample after it has been dried to constant weight (recorded as m0), immerse it completely in deionized water at 25℃ for 24h, take it out and gently wipe off the surface water of the sample with a damp towel, weigh it immediately (recorded as m1), and calculate the mass water absorption rate according to the formula "water absorption rate = (m1-m0) / m0×100%".

[0122] (3) Thermal shock resistance: The water-cooled thermal cycling method was used for testing. The sample size was 100mm×100mm×20mm. The sample was first placed in a muffle furnace at 800℃ for 30min, then quickly removed and immersed in 25℃ deionized water for 5min to cool. The sample was then removed and placed back in the muffle furnace and heated to 800℃. This was one thermal shock cycle. The number of cycles in which the sample first showed macroscopic cracks and slag was recorded. At the same time, the compressive strength retention rate after 10 cycles was tested (compressive strength after cycles / initial compressive strength × 100%).

[0123] The test results are shown in Table 1: Table 1 Performance Test Results

[0124] As shown in Table 1, the performance test data indicate that the aerogel composite materials prepared in Examples 1-4 of this application have achieved excellent performance in terms of thermal insulation, high temperature resistance, and mechanical strength compared with the ordinary basalt-aerogel homogeneous composite materials described in Comparative Examples 1-3.

[0125] In terms of thermal insulation and temperature resistance, this material exhibits excellent high-temperature stability. Specifically, its thermal conductivity at room temperature (25℃) is 0.021-0.024 W / (m·K); even at a high temperature of 800℃, the thermal conductivity only remains at 0.071-0.081 W / (m·K), a reduction of 32%-38% compared to Comparative Example 1. Furthermore, the long-term service temperature of this composite material can reach 820-980℃, and the short-term service temperature can reach as high as 1180℃. After 1000 hours of continuous use at a constant temperature of 800℃, the composite material showed no significant thermal shrinkage, with a shrinkage rate controlled at 0.8%-1.8%, and no cracking or delamination was observed, demonstrating good structural integrity.

[0126] In terms of mechanical properties and physical characteristics, this composite material effectively overcomes the defects of traditional aerogel materials, such as high brittleness and low strength. Tests show that its compressive strength is 2.1-2.8 MPa, tensile strength is 0.85-1.1 MPa, and flexural strength is 1.25-1.80 MPa. Furthermore, the material has a bulk density of 0.21-0.37 g / cm³ and a water absorption rate of 2.1%-4.7%. In thermal shock resistance tests (10 cycles from -40℃ to 800℃), the material showed no damage or deformation, demonstrating good environmental adaptability and reliability.

[0127] In the description of this specification, the references to terms such as "one embodiment / mode," "some embodiments / modes," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment / mode or example is included in at least one embodiment / mode or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment / mode or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments / modes or examples. Furthermore, without contradiction, those skilled in the art can combine and integrate the different embodiments / modes or examples described in this specification, as well as the features of different embodiments / modes or examples.

[0128] It should be noted that in this invention, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, technology, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, technology, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, technology, article, or apparatus that includes said element. In this invention, "a plurality of" means at least two, such as two, three, etc., unless otherwise expressly specified.

[0129] The above description is merely a specific embodiment of the present invention, enabling those skilled in the art to understand or implement the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the present invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features of the invention herein.

Claims

1. An aerogel composite material, characterized in that, The composite material includes a first layer and a second layer disposed opposite to each other, and a gradient transition region disposed between the first layer and the second layer, wherein, along the thickness direction from the first layer to the second layer, the content of basalt fiber phase in the composite material decreases gradually, and the content of silica aerogel phase increases gradually. In the gradient transition zone, a nano-transition layer is provided at the interface between the basalt fibrous phase and the silica aerogel phase. The nano-transition layer includes nano-silica and a silane coupling agent.

2. The aerogel composite material as described in claim 1, characterized in that, In the first layer, the basalt fibrous phase has a mass percentage of 62-78 wt%, and the silica aerogel phase has a mass percentage of 22-38 wt%; and / or, In the second layer, the basalt fiber phase has a mass percentage of 25-47 wt%, and the silica aerogel phase has a mass percentage of 53-75 wt%.

3. The aerogel composite material as described in claim 1, characterized in that, In the nano-transition layer, the mass ratio of the nano-silica to the silane coupling agent is 100:(7-13); and / or, The thickness of the nano-transition layer is 8-18 μm.

4. The aerogel composite material as described in claim 1, characterized in that, The composite material also has a multi-level pore gradient structure, and the pore size distribution of the multi-level pore structure varies in a gradient along the thickness direction from the first layer to the second layer.

5. The aerogel composite material as described in claim 4, characterized in that, In the first layer, the basalt fibrous phase has an average pore size of 65-185 μm, and the silica aerogel phase has an average pore size of 85-98 nm; and / or, In the second layer, the average pore size of the basalt fiber phase is 120-280 μm, and the average pore size of the silica aerogel phase is 25-48 nm.

6. A method for preparing an aerogel composite material as described in any one of claims 1-5, characterized in that, include: Basalt fibers are mixed with a binder and a molding process is used to prepare a preform with a gradient distribution of basalt fiber content, resulting in a basalt fiber gradient preform. The preform has a first region and a second region that are arranged opposite to each other along the thickness direction. Nano-silica and silane coupling agent are dispersed in a solvent to obtain a nano-transition layer coating solution; The transition region between the first region and the second region is brought into contact with the nano-transition layer coating liquid, and then the preform is impregnated with a gradient concentration of silica sol along the direction from the first region to the second region. The impregnated preform is then gelled to obtain a composite preform. The composite preform is dried using a gradient heating process to obtain the aerogel composite material.

7. The preparation method according to claim 6, characterized in that, The molding process uses a pressing pressure of 0.7-1.3 MPa, a molding temperature of 105-118℃, and a holding time of 2.5-3.5 h.

8. The preparation method according to claim 6, characterized in that, The concentration gradient distribution of the silica sol is specifically as follows: the sol concentration corresponding to the first region is 22-38 wt%, the sol concentration corresponding to the second region is 53-75 wt%, and the sol concentration in the transition region exhibits a gradient change; and / or, The impregnation process includes vacuum impregnation, with a vacuum degree of -0.085 to -0.098 MPa.

9. The preparation method according to claim 6, characterized in that, The drying process includes: raising the drying temperature from 50°C to 120°C at a rate of 6-9°C / h; and holding the temperature for 1.2-1.8h for every 20°C increase during the drying process until the moisture content of the composite green body is ≤0.9%.

10. A high-temperature thermal insulation component, characterized in that, The aerogel composite material includes any one of claims 1-5, wherein the first layer is disposed toward the heat source.